Advances in 3D printing of composite scaffolds for the repairment of bone tissue associated defects. (3rd February 2022) - Anandhapadman, Ashwin; Venkateswaran, Ajay; Jayaraman, Hariharan; Veerabadran Ghone, Nalinkanth
Abstract: The conventional methods of using autografts and allografts for repairing defects in bone, the osteochondral bone, and the cartilage tissue have many disadvantages, like donor site morbidity and shortage of donors. Moreover, only 30% of the implanted grafts are shown to be successful in treating the defects. Hence, exploring alternative techniques such as tissue engineering to treat bone tissue associated defects is promising as it eliminates the above‐mentioned limitations. To enhance the mechanical and biological properties of the tissue engineered product, it is essential to fabricate the scaffold used in tissue engineering by the combination of various biomaterials. Three‐dimensional (3D) printing, with its ability to print composite materials and with complex geometry seems to have a huge potential in scaffold fabrication technique for engineering bone associated tissues. This review summarizes the recent applications and future perspectives of 3D printing technologies in the fabrication of composite scaffolds used in bone, osteochondral, and cartilage tissue engineering. Key developments in the field of 3D printing technologies involves the incorporation of various biomaterials and cells in printing composite scaffolds mimicking physiologically relevant complex geometry and gradient porosity. Much recently, the emerging trend of printing smart scaffolds which can respond to external stimulus such as temperature, pH and magnetic field, known as 4D printing is gaining immense popularity and can be considered as the future of 3D printing applications in the field of tissue engineering.